PENGEMBANGAN MEDIA POP UP STORY BOOK BERBASIS PROBLEM BASED LEARNING PADA PELAJARAN PENDIDIKAN PANCASILA DI KELAS III SEKOLAH DASAR - Afaf Izzah Kamilah; Otib Satibi Hidayat; Uswatun Hasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research and development aims to describe the development process and determine the feasibility quality of the Pop-Up Story Book product based on Problem-Based Learning. The research method used is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The data analysis techniques used were quantitative and qualitative data analysis techniques with research subjects including 3 experts (language expert, media expert, material expert), 3 students for one-to-one testing, 8 students for the small group test, and 16 students for the field test. Data collection was carried out through observation, interviews, and questionnaires. The results of this study show the feasibility level of the product based on the validation tests: 63% from the language expert, 91% from the media expert, 95% from the material expert. Student trials obtained a feasibility percentage of 100% in the one-to-one test, 95% in the small group test, and 98% in the field test. Based on the assessment from the expert validations and student trials, it can be concluded that the development of the Pop-Up Story Book media is Highly Feasible and can be implemented as a learning medium in the Pancasila education learning process for Grade 3 Elementary School.